Rejection of the Terms of Polygamy from the Perspective of the Book Al-Mughnī by Ibnu Qudāmah: A Normative Study of the Hanbali School - Badrihatun Hasanah (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2025)
This study discusses the rejection of the conditions for polygamy from a fiqh perspective, particularly within the Hanbali school of thought, through a study of Ibn Qudāmah's book Al-Mughnī . Polygamy is an issue that has not only legal dimensions, but also social and ethical dimensions, especially related to justice, the consent of the first wife, and family welfare. In the Hanbali tradition, Ibn Qudāmah is known as one of the figures who systematically and normatively reorganized the thoughts of Ahmad ibn Hanbal, including in discussions on marriage and polygamy. This study aims to determine how the Hanbali school of thought, through Ibn Qudāmah's work, views the conditions for polygamy such as justice, financial capacity, and the wife's permission. This study uses a qualitative approach with a normative study method on the primary text ( Al-Mughnī ) and is supported by secondary texts in the comparative fiqh literature of the schools. The results of the study indicate that the Hanbali school, as explained by Ibn Qudāmah, in principle does not require the permission of the first wife as a valid basis for polygamy, but emphasizes the requirement of justice as a moral requirement and legal consequence. The rejection of additional requirements such as the wife's permission is seen as an effort to maintain the authority of the text and reject sharia taklīf that is not based on qat'i evidence. This study contributes to the discourse of Islamic family law, particularly in distinguishing between normative requirements based on texts and administrative requirements based on benefits and the contemporary context.